Validation Analysis of Learning Development on Optic Material with Core Learning Model - Eva Fasihah; Nurul Hidayah Al Mubarokah (SAGA: Journal of Technology and Information System, 2023)
This research is an activity process to produce learning tools that are developed in valid optical material, with the development path using the CORE learning model. The tools developed are syllabus, lesson plans, textbooks, worksheets and Critical Thinking Ability Test. However, in this paper, it is only focused on the validation test process through construct and content validation tests on the development of the device made. The final result of this research is to produce a valid learning device development product.